Effect of different pretreatment methods on pore structure of activated carbon. Issue 1 (January 2021) - Yang, H; Liu, J; Pang, B; Chi, J
Abstract: The effects of pretreatment on the pore structure of activated carbon were studied by the methods of water washing, acid washing, alkali washing and a combination of acid washing and alkali washing. It can be known from experiments that water washing has a cleaning effect on activated carbon, while acid washing helps to open the micropores of activated carbon and improve its porosity. Sodium hydroxide solution has an etching effect on activated carbon, which can increase the porosity and average particle size of activated carbon. All the pretreatment methods in this article can improve the adsorption capacity of activated carbon for nitrogen, and the pretreatment by dilute hydrochloric acid is tested to be the most effective.